Does N-terminal pro-brain natriuretic peptide correlate with measured shunt fraction in children with septal defects?*. (10th April 2015) - Ozyurt, Abdullah; Baykan, Ali; Argun, Mustafa; Pamukcu, Ozge; Uzum, Kazim; Narin, Figen; Narin, Nazmi
Abstract: Background: The aim of this study was to investigate the potential role of N-terminal pro-brain natriuretic peptide in the assessment of shunt severity and invasive haemodynamic parameters in children with atrial septal defects and ventricular septal defects. Methods: This is a prospective, controlled (n:62), observational study. Correlation analysis was performed between N-terminal pro-brain natriuretic peptide levels and various invasive haemodynamic measurements in 127 children (ventricular septal defect: 64; atrial septal defect: 63). A ratio of pulmonary to systemic blood flow (Qp/Qs⩾1.5) was considered to indicate a significant shunt. Results: Statistically significant relationship was found between the mean N-terminal pro-brain natriuretic peptide values of the patients, with Qp/Qs⩾1.5 in both defect types and control group. For ventricular septal defect, N-terminal pro-brain natriuretic peptide level⩾113.5 pg/ml was associated with high specificity and sensitivity for determining the significant shunt. In addition, the cut-off point for determining the significant shunt for atrial septal defect was 57.9 pg/ml. Significant positive correlation was found between all invasive haemodynamic parameters and N-terminal pro-brain natriuretic peptide levels in patients with ventricular septal defects. Whereas significant positive correlation was found only between mean pulmonary artery pressure, right ventricular end-diastolic pressure, and systemic pressure to pulmonary pressure ratio and N-terminal pro-brain natriuretic peptide levels in patients with atrial septal defects. Conclusion: Our study demonstrated that the N-terminal pro-brain natriuretic peptide measurements could be used as a supporting parameter in determining significance of the shunt.